2021
DOI: 10.1016/j.urology.2020.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Association of Surgical Delay and Overall Survival in Patients With T2 Renal Masses: Implications for Critical Clinical Decision-making During the COVID-19 Pandemic

Abstract: OBJECTIVE To test for an association between surgical delay and overall survival (OS) for patients with T2 renal masses. Many health care systems are balancing resources to manage the current COVID-19 pandemic, which may result in surgical delay for patients with large renal masses. METHODS Using Cox proportional hazard models, we analyzed data from the National Cancer Database for patients undergoing extirpative surgery for clinical T2N0M0 renal masses between 2004 and 2015. Study outcomes were to assess for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 27 publications
0
15
1
Order By: Relevance
“…Treatment delay had significant lower overall survival rate per 14 day-delay (HR = 1.06 [1.05-1.07]; (p < 0.001)) ( Grass et al, 2020 ). Ginsburg et al estimated an approximative 10% increase in hazard ratio of all-cause mortality for each month interval between diagnosis and surgery (HR = 1.10 [1.06-1.14]; (p < 0.001)) ( Ginsburg et al, 2020 ). Similarly, a study in Taiwan showed that patients who received treatment between 90 and 180 days after diagnosis had more than 30% risk of death than those who received treatment within 90 days (HR = 1.33; [1.02-1.72]; (p < 0.05)) ( Chen et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Treatment delay had significant lower overall survival rate per 14 day-delay (HR = 1.06 [1.05-1.07]; (p < 0.001)) ( Grass et al, 2020 ). Ginsburg et al estimated an approximative 10% increase in hazard ratio of all-cause mortality for each month interval between diagnosis and surgery (HR = 1.10 [1.06-1.14]; (p < 0.001)) ( Ginsburg et al, 2020 ). Similarly, a study in Taiwan showed that patients who received treatment between 90 and 180 days after diagnosis had more than 30% risk of death than those who received treatment within 90 days (HR = 1.33; [1.02-1.72]; (p < 0.05)) ( Chen et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…In May 2020, 79% of cancer patients in active treatment experienced some delay in their health care because of COVID-19 [ 56 ]; which may affect long-term survival because of suboptimal or delayed care [ 8 , 13 , 39 , 40 , 41 , 55 , 57 , 58 , 59 ]. Together, these trends can exacerbate pre-existing disparities in cancer morbidity and mortality experiences by Black/African American and Hispanic/Latinx adults [ 47 , 60 , 61 , 62 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although a delay of 2–3 months are unlikely to affect the oncological outcomes, a further delay has been shown to affect outcomes for some urological malignancies. Surgical delay in MIBC greater than 12 weeks, 5–6 months delay in T2 RCC, delay greater than 120 days for high-grade upper tract urothelial cancer are all associated with a negative impact on the overall survival [ [14] , [15] , [16] ]. This is in contrast to patients’ perspective, where a recent survey of urological patients conducted in Italy showed that majority of patients preferred to delay the surgery and considered the risk of COVID-19 more harmful than delaying surgery [ 17 ].…”
Section: Discussionmentioning
confidence: 99%